2005
DOI: 10.1080/14756360500043448
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structure–activity relationships of analogs of EM-652 (acolbifene), a pure selective estrogen receptor modulator. Study of nitrogen substitution

Abstract: EM-652 (acolbifene) analogs have been synthesized as selective estrogen receptor modulators. Substitution on the nitrogen atom of these 2H-1-benzopyran derivatives has been studied for its influence on antiestrogenic activity. Binding to the rat estrogen receptor, inhibition of estradiol-stimulated proliferation of T-47D breast cancer cells, as well as antiuterotrophic and uterotrophic activities in ovariectomized mice have been evaluated. 2H-1-Benzopyran 1b (EM-343, racemic form of EM-652), which contains a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…2b ). The unsubstituted pyrrolidine, OP-1156, induced AP activity 40%, in line with the increased uterine wet weight in ovariectomized mice previously reported for this compound 38 . In contrast to the antagonist activity observed for 3R-substituted pyrrolidine of OP-1074, the 3S-substituted analog, OP-1154, induced AP activity 39% and did not completely antagonize E2-stimulated AP activity.…”
Section: Resultssupporting
confidence: 85%
“…2b ). The unsubstituted pyrrolidine, OP-1156, induced AP activity 40%, in line with the increased uterine wet weight in ovariectomized mice previously reported for this compound 38 . In contrast to the antagonist activity observed for 3R-substituted pyrrolidine of OP-1074, the 3S-substituted analog, OP-1154, induced AP activity 39% and did not completely antagonize E2-stimulated AP activity.…”
Section: Resultssupporting
confidence: 85%
“…Exploration of the side chains of dihydrobenzoxathiins compounds such as compound 23 is the foundation of the discovery of basic amino side chain SERDs (Figure ). …”
Section: Recent Development Of Serdsmentioning
confidence: 99%
“…Exploration of the side chains of dihydrobenzoxathiins compounds such as compound 23 is the foundation of the discovery of basic amino side chain SERDs (Figure 7). 125 26) is one of the second generation of nonsteroidal acrylic acid SERDs developed from GW 5638 (24). In 2005, Wu et al reported two antiestrogens, compound 24 and its hydroxylated metabolite GW7604 (25), with a triphenylethylene scaffold similar to 4hydroxytamoxifen (Figure 8).…”
Section: Role Of Erα In the Mechanism Of Acquiredmentioning
confidence: 99%
“…EM-800 is a well-studied precursor of acolbifene which was found to be safe and tolerable [196,197]. It is orally active but lacks agonistic activity in the endometrium, thereby reducing the chances of developing uterine cancer [198][199][200]. The drug was found to have partial cross-resistance with tamoxifen [198].…”
Section: Selective Estrogen Receptor Modulators (Serms)mentioning
confidence: 99%